Point load effect on the buried polyolefin pipes lifetime. Issue 1 (30th October 2015) - Majer, Z.; Hutař, P.; Frank, A.; Ševčík, M.; Zouhar, M.; Pinter, G.; Náhlík, L.
Abstract : Polymer pipe lifetime is conventionally estimated by internal pressure test. However, important for service are also other types of loading as: additional bending, different type of external loading from sand embedding, or effect of the residual stresses. One of the dangerous type of loading is so‐called "point load" caused, for example, by stones in the soil. The present article is focused on the numerical prediction of this effect on the pipe lifetime. For the lifetime estimation of a polymer pipe under point loading, an approach based on combination of numerical calculation and experimental measurements was used. A special numerical algorithm, which optimizes modeled crack front shape according to the real one during simulation of crack propagation, was proposed. Finally, an analytical relationship for the estimation of fracture parameters of propagating crack across the pipe wall crucial for the pipe lifetime estimation is presented in the paper. A significant reduction of the residual lifetime was found for the cracked pipe loaded by additional point load (consideration of indentation effects of stones in the soil) in comparison with pipe loaded by internal pressure only. The approach presented contributes to the safer service of polyolefin pipes. POLYM. ENG. SCI., 56:79–86, 2016. © 2015 Society of Plastics Engineers